Tolakinese Language Attitude toward Tolaki-Dialect of Mekongga in Kolaka District - S. Sarmadan; S. Samsuddin (Universitas Sembilanbelas November Kolaka, 2017)
The purpose of this research is to describe the language attitude of Tolakinese people toward Mekongga dialect. This research applied qualitative approach. The place of this research was carried out in Kolaka District. Techniques of collecting data through interviews, observation, documents. Based on the results of data analysis found that Tolaki ethnic community in Kolaka experiencing relatively negative language attitude toward Mekongga dialect. This was because the speakers of Mekongga dialect began to feel less confident in using the local language. Another thing that caused it is the presence of cross-breeding. A family with parents of different ethnic groups, then it is probable that their children do not master one of the languages of their parents, even each parents' language is not controlled by the child. However, there are actually some speakers who show their caring attitude towards the Tolaki language of Mekongga dialect. It is a positive signal that there is still a Tolakinese of Mekongga dialect community who is affectionate and caring about the local language. But the problem is they have not been able to do something meaningful in order to preserve the local language. The first step they can take is to show a more positive language attitude using Mekongga dialect in daily communication, especially in the family environment, i.e to children, husbands, and wives. In addition to the low language attitudes of the community, this also cannot be separated from the lack of significant government attention to regional languages. This is evidenced by the implementation of local language learning content that is still below the standards, both in terms of teacher availability and teacher competence. It is also in line with the government's policy on naming roads and public facilities that are less aligned to the preservation of the Tolaki-dialect of Mekongga.